Exploration of mathematical concepts in Batik Truntum Surakarta - Adi Nurcahyo; Naufal Ishartono; Alma Yasinta Candra Pratiwi; Mohamad Waluyo (IKIP Siliwangi and I-MES, 2024)
This research investigates the mathematical concepts embedded within Batik Truntum motifs, including geometry, analysis, arithmetic, and algebra. Employing a qualitative methodology with an ethnographic approach, the study addresses four critical questions: